A Simple and Effective Process to Join Coated Super-conductors at a Low Resistance. Issue 3 (March 2018) - Han, Zhang; Guangtong, Ma; Xingtian, Li; Jinfang, Peng; Zhibiao, Xu; Tianyong, Gong; Minhao, Zhu
Abstract : Abstract: With recent advances on the performance of the YBCO coated conductor (CC) tape, its attractive perspectives for application have opened up for us. Joining process of CC tapes is inevitable for development of coated superconductor based apparatuses where single tape is not long enough or needs to be looped. Generally the joint was completed at a certain temperature and under a constant pressure that were investigated in prior literatures. Because the CC tape is very thin, and easy to damage because of deformation in some region of the tape, the surface of the joint making table should be flat and smooth enough, which have not received serious attention yet. Meanwhile, the smoothness of the pressing table is crucial to obtain the joint with low resistance. In this paper, a simple and effective joint of coated superconductor tapes making process depending on a soldering table with high smoothness less than 5 μm/100 mm was investigated. In the process, the non-superconducting lapped joint method with face-to-face configuration was employed, and the solder layer thickness and the joint lapped length varied. The current-voltage characteristic of the jointed tapes was measured in liquid nitrogen bath by a standard four-probe technique. The joint with sufficiently low resistance of 6.3 nΩ was easily achieved with a lapped length of 14 cm, which is ascribed to the use of a soldering table with high smoothness. In addition, the joints microstructure was observed by the metallographic microscope and scanning electron microscopy (SEM) to reveal the distribution of the solder between the joined CC tapes.